What Goes Around Comes Around : Designing Innovative Learning Events to Improve Relationships and Program Results in the Philippines SEF Program - Verdote, Noel N.; Fernando-Pacua, Marianna Alfa (International Finance Corporation, Washington, DC, 2014)
Since its launch in 2009, the Sustainable Energy Finance (SEF) Program in the Philippines has worked with four partner banks Bank of the Philippine Islands (BPI), BDO Unibank, Inc. (BDO), China Banking Corp. (Chinabank), and BPI Globe BanKO (BanKO) to help them identify and develop nearly 300 energy efficiency/renewable energy (EE/RE) projects. These banks have directly loaned $439 million to finance 118 of these projects, resulting in an annual savings of nearly 115,000 megawatt hours of electricity and annual generation of 951,613 megawatt hours of clean energy. The annual reduction of greenhouse gas emissions reached about 1 million metric tons a year as of December 2013. The project received an award under the financing for climate-friendly investments pillar by the Momentum for Change 2013 Lighthouse Activities, an initiative of the United Nations Framework Convention on Climate Change in partnership with the World Economic Forum. Underlying these achievements is SEF s devotion to helping bank staff und rstand energy efficiency and renewable energy, and how financing these projects benefit both the banks and their clients. Over the years, we ve learned a lot ourselves about creating learning events for bank staff and how to make these training events more appealing, more enjoyable, and ultimately more effective.